2007
DOI: 10.1109/led.2007.906932
|View full text |Cite
|
Sign up to set email alerts
|

The Leakage Current of the Schottky Contact on the Mesa Edge of AlGaN/GaN Heterostructure

Abstract: A test structure, which is called the ridge-furrow structure, is used to evaluate the leakage current of the Schottky contact on the mesa edge of an AlGaN/GaN heterostructure. The mesa edge leakage currents were measured at different temperatures from 300 to 500 K and analyzed. The conduction-band-edge energy distribution at the mesa edge is simulated by the Integrated Systems Engineering Technology Computer-Aided Design. Based on the simulation results, the electric field strength can be obtained as a functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…11 Zhang et al 7 analyzed the leakage current mechanisms in the Schottky contacts of both n-GaN and AlGaN/GaN at different temperatures and concluded that tunneling current dominates at temperatures below 150 K, whereas the Frenkel-Poole emission dominates at temperatures higher than 250 K. Miller et al 8 have shown that the reverse-bias leakage in AlGaN/GaN can be analyzed in a conventional tunneling model. The effects of the dislocations and defects states, in the reverse-bias leakage, have been suggested by several studies for GaN and Al x Ga 1−x N heterostructures 4,6,7 wherein defects, in particular dislocations, might play an important role in reverse-bias leakage. 4,7,8 However, to date, no investigation has been made to analyze the leakage current of the mechanisms of Schottky contacts on Al 1−x In x N / AlN/ GaN heterostructures.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…11 Zhang et al 7 analyzed the leakage current mechanisms in the Schottky contacts of both n-GaN and AlGaN/GaN at different temperatures and concluded that tunneling current dominates at temperatures below 150 K, whereas the Frenkel-Poole emission dominates at temperatures higher than 250 K. Miller et al 8 have shown that the reverse-bias leakage in AlGaN/GaN can be analyzed in a conventional tunneling model. The effects of the dislocations and defects states, in the reverse-bias leakage, have been suggested by several studies for GaN and Al x Ga 1−x N heterostructures 4,6,7 wherein defects, in particular dislocations, might play an important role in reverse-bias leakage. 4,7,8 However, to date, no investigation has been made to analyze the leakage current of the mechanisms of Schottky contacts on Al 1−x In x N / AlN/ GaN heterostructures.…”
mentioning
confidence: 98%
“…[4][5][6]12 In the case of dominant dislocation-related conductivity in the leakage current at room temperature for Al 0.83 In 0.17 N / AlN/ GaN Schottky diodes, we required in our analysis that a single transport mechanism must accurately describe the current flow. The transport model based on Frenkel-Poole emission satisfied this criterion and gives realistic values for the necessary physical parameters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements were performed on 0.25 μm gate length AlGaN/GaN HEMTs fabricated in a Chalmers in-house MMIC process [9]. For the noise measurements, devices with 4 × 75 μm gate periphery were used.…”
Section: Effects Of Gate Bias Stress On Noise Performancementioning
confidence: 99%
“…We specifically address the case where the devices are isolated using an etched mesa, with the gate fingers extending outside the mesa and directly contacting the GaN channel through the mesa sidewall, giving rise to an additional conduction path for the gate current. The effect of this leakage path on the reverse leakage has been studied in [9], but the effects on device robustness have previously not been tested. Moreover, it is shown how degradation tests on device level can be used to analyze or optimize robustness of LNAs using circuit level simulations.…”
mentioning
confidence: 99%